Hazelnut as Ingredient in Dairy Sheep Diet: Effect on Sensory and Volatile Profile of Cheese - Caccamo, Margherita; Valenti, Bernardo; Luciano, Giuseppe; Priolo, Alessandro; Rapisarda, Teresa; Belvedere, Giovanni; Marino, Vita Maria; Esposto, Sonia; Taticchi, Agnese; Servili, Maurizio; Pauselli, Mariano (Frontiers in Nutrition, 2019)
The opportunity of replacing expensive feedstuffs with agro-industrial by-products in the diet of food producing animals is raising increasing interest while addressing global concern for the scarcity of natural resources and environmental impact of livestock farming. Hazelnut peels, rich in fiber and vitamins and characterized by a high concentration of fats, is considered a suitable ingredient to be included in the diet of ruminants. The aim of this research was to assess the effect of dietary hazelnut peels on the chemical and sensory properties of sheep cheese during refrigerated storage. To this purpose, 20 Comisana lactating ewes were randomly assigned to two experimental groups, control (C) and hazelnut peels (HP), balanced for parity, milk yield and body weight. Bulk milk collected from the 2 groups was used to produce 5 Pecorino cheeses for each group. After 40 d of ageing, each cheese of each experimental group was divided into 3 pieces: 1 piece was sampled for analyses (C0, HP0) and 2 were wrapped in PVC film, simulating the condition of pre-wrapped products, and analysed after 7 (C7, HP7) and 14 days of storage (C14, HP14) at 8°C with 80% moisture. The cheeses were analysed for chemical and fatty acid composition, sensory analysis, odour active compounds and SmartNose. As expected, HP cheeses presented a higher lipid content compared to C, a lower content in SFA and PUFA, and a greater content in MUFA. A triangle test revealed a clear distinction between the 2 groups (α=0.01) The sensory profile showed a significant effect on holes (P<0.05) and a marginal production of off-flavours linked to spicy and acid attributes for HP cheeses The volatile profile of C and HP cheese samples showed a good similarity, partially explained by the short ripening time and the absence of 2-nonanone in HP7, suggesting a higher antioxidant protection grade of this cheese compared to the others. These results were confirmed by Smart Nose analysis. Further studies on vitamin content should be conducted in order to investigate the interactions between the presence of antioxidant volatile compounds and the oxidative stability of ewe cheese.